Future Potential of Bio Polymeric Nanoparticles: Synthesis, Characterization and Their Promising Applications - Anjum, M. Reshma; Sowmika, Sagi; Sravya, Bojjala; Golla, Narasimha (Archives of Business Research, 2024)
The bio polymeric nanoparticles are a group of nanoparticles that are constructed from natural polymers found in biological species. Examples include proteins (e.g.; collagen, gelatine, zein & albumin), cationic polypeptides (e.g.; polyimide), protein mimicking polypeptides (e.g.; polypeptide like molecules) and polysaccharides (e.g. hyaluronic acid, chitosan & starch). These nanoparticles are being developed right now to address issues with toxicity, biocompatibility, and biodegradability. Many industries employ both metallic nanoparticles (NPs) and bio polymeric nanoparticles (BPNPs), however BPNPs are safer and better for the environment. Currently, BPNPs are being used extensively in the chemical, biological, food, and diagnostic equipment industries as well as the household. They have attracted great attention because of their multiple applications in biomedicine. The nanoparticles synthesis methods such as emulsification, desolvation, coacervation, and electrospray drying are discussed. Characterization techniques includes dynamic light scattering, transmission electron microscopy, scanning electron microscopy, nuclear magnetic resonance spectroscopy, atomic force microscopy, x-ray diffraction, the fourier transformation infrared spectroscopy, and thermal analysis. Applications in the areas of packaging, water purification, food industry and medicine are described, along with a positive future outlook.